A 10-Year Study of the Trend of Accidental Falls in the Elderly in a Japanese Hospital - Takekawa, Toru; Obuchi, Kei; Watanabe, Shu; Yamada, Naoki; Abo, Masahiro (Zeitschrift für Orthopädie und Unfallchirurgie, 2024)
Elderly people are prone to falls. We established the Falls Prevention Working Group (FPWG) at our hospital in 2015 to reduce the number of falls during hospitalization. This study compared the trend of in-hospital falls in the elderly in two time periods (2008/9 and 2018/9) and determined the effects of FPWG-implemented measures. Using medical records, we counted the monthly number of falls suffered by patients during hospitalization in April 2008-March 2009 and April 2018-March 2019. We also categorized the falls according to the severity of fall-related complications.A total of 3609 hospital falls were recorded during the 2008–2019 period (2008/9: n = 433, 2018/9: n = 324). Falls were more common in patients aged 70–79 in 2008/9 but were noted in those aged ≥ 80 in 2018/9. The mean number of falls/month (27.3 ± 6.4, range: 12–45) was stable throughout the year. The incidence of falls in 2018/9 (1.90/1000 per persons per day) was significantly lower than in 2008/9 (2.30/1000, p = 0.006). Level ≥ 3b accidents, reflecting serious accidents with complications, were encountered in 12 of 433 accidents in 2008/9 compared with significantly fewer accidents (2 of the same severity among 324 accidents) in 2018/9 (p = 0.030).Our results showed a decrease in in-hospital falls in 2018/9 and that the sufferers were older relative to 10 years earlier. A multidisciplinary team should recommend measures to prevent falls and an environment “resilient” to falls, and encourage patients to be aware of possible falls.
Keywords: accidental falls; interdisciplinary team; longevity; risk management; prevention and control